Effect of AlGaN undershell on the cathodoluminescence properties of coaxial GaInN/GaN multiple-quantum-shells nanowires. Issue 40 (8th October 2019) - Lu, Weifang; Sone, Naoki; Goto, Nanami; Iida, Kazuyoshi; Suzuki, Atsushi; Han, Dong-Pyo; Iwaya, Motoaki; Tekeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract : An impressive enhancement of cathodoluminescence was achieved in coaxial GaInN/GaN multiple-quantum-shells nanowires by employing an AlGaN undershell for trapping point defects. Abstract : Coaxial GaInN/GaN multiple-quantum-shells (MQSs) nanowires (NWs) were grown on an n-type GaN/sapphire template employing selective growth by metal–organic chemical vapour deposition (MOCVD). To improve the cathodoluminescence (CL) emission intensity, an AlGaN shell was grown underneath the MQS active structures. By controlling the growth temperature and duration, an impressive and up to 11-fold enhancement of CL intensity is achieved at the top area of the GaInN/GaN MQS NWs. The spatial distribution of Al composition in the AlGaN undershell was assessed as a function of position along the NW and analysed by energy-dispersive X-ray measurement and CL characterisation. By introducing an AlGaN shell underneath GaInN/GaN MQS, the diffusion of point defects from the n-core to MQS is effectively suppressed because of the lower formation energy of vacancies-complexes in AlGaN in comparison to GaN. Moreover, the spatial distribution of Al and In was attributed to the insufficient delivery of gas precursors to the bottom of the NWs and the anisotropy diffusion on the nonpolar m -planes. This investigation can shed light on the effect of the AlGaN undershell on improving the emission efficiency of NW-based white and micro-light-emitting diodes (LEDs).